Syarah Hadith with Saga: Methodological Study of the Book of An-Nail Al-Hatsîts Fî Hikâyât Al-Hadîts by Al Imam Al Faqih Abu Laits As-Samarqandi - Nuralita, Fadila Ikke; Ahmadi, Rizqa; Noorhidayati, Salamah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article investigates the syarah of the book an-Nail al-Hatsîts fî Hikâyât al-Hadîts (NHfHH) by Al-Imam Al Faqih Abu Laits As-Samarqandi with a focus on the study of syarah hadith methodology. This work by As-Samarqandi is classified as a book in the Sufism genre, which is arranged thematically and contains various explanations (syarah) of the saga. This research employs a qualitative design with literature research methods. Next, hadith data was collected from primary sources, namely NHfHH, and then the data was read by using the takhrij hadith method to trace the hadith reference sources. This research found out that NHfHH by As-Samarqandi is using the ijmali syarah method, which explains its syarah globally. Next, the writing of the syarah is originated from companions, tabi'in, Sufism, explanation of verses of the Al-Qur’an, verses of poetry, and unidentified sources. The sharia style of this book has five varieties: fiqh, social, Sufi lore, linguistics and education. In addition, As-Samarqandi uses expository narration based on actual facts and data. A suggestive narrative is based on events that involve the reader's imagination, so it is equipped with character dialogue, scenes of events, and resolution. The written book is comprehensively divided into chapters according to what society needs and is a tool for socialization about social values, motivation, and uplifting the soul. Thus, this makes this work accessible to understand, educates people on how to behave and do good deeds, and allows them to tolerate various events. Apart from that, it teaches an attitude of getting closer to Allah and trying to change a bad personality into a good one. In brief, NHfHH proves that the style of writing syarah hadith books has developed following society's need for prophetic messages.